2019
DOI: 10.1186/s13244-019-0799-2
|View full text |Cite
|
Sign up to set email alerts
|

Mentorship in academic radiology: why it matters

Abstract: Mentorship plays a critical role in the success of academic radiologists. Faculty members with mentors have better career opportunities, publish more papers, receive more research grants, and have greater overall career satisfaction. However, with the increasing focus on clinical productivity, pressure on turnaround times, and the difficult funding climate, effective mentoring in academic radiology can be challenging. The high prevalence of "burnout" among radiologists makes mentorship even more important. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 75 publications
0
46
0
3
Order By: Relevance
“…23 Several studies have also associated mentorship with improved career satisfaction. [24][25][26][27][28] TA B L E 1 Factors associated with lower burnout Focusing 20% of the professional time on work found meaningful by the individual 22 Achieving balance with non-clinical activities 7,14,19,23,32 Attending CME conferences 2,23 Teaching role 22,23 Professional leadership roles 7,23 Sufficient time for personal life 4,14,21,39 Mentorship 27,29 Department leadership that fosters a sense of partnership and physician engagement 42…”
Section: Research On Specific Career Aspects That Are Associated Withmentioning
confidence: 99%
“…23 Several studies have also associated mentorship with improved career satisfaction. [24][25][26][27][28] TA B L E 1 Factors associated with lower burnout Focusing 20% of the professional time on work found meaningful by the individual 22 Achieving balance with non-clinical activities 7,14,19,23,32 Attending CME conferences 2,23 Teaching role 22,23 Professional leadership roles 7,23 Sufficient time for personal life 4,14,21,39 Mentorship 27,29 Department leadership that fosters a sense of partnership and physician engagement 42…”
Section: Research On Specific Career Aspects That Are Associated Withmentioning
confidence: 99%
“…Benefits of mentorship in academic medicine include better career opportunities, greater career satisfaction, and better work-life integration of faculty with mentors [1][2][3][4].…”
Section: Discussionmentioning
confidence: 99%
“…Mentorship plays a critical role in the success of academic radiologists. Studies have shown that faculty with mentors have better career opportunities, are promoted quicker, publish more papers, receive more research grants, and have lower rates of burnout and greater career satisfaction [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Not only can mentorship help the mentee in improving clinical efficiency, but the mentee can also receive professional support and advice. 35 This aided in addressing the challenge of adapting to a new system at the workplace and provided crucial support in improving their radiography specific competencies. However, this required significant operational planningdengaging with roster planner(s) on best-fit distribution of newly joined radiographers, while balancing the needs of professional development and the required minimum functional manpower in each area.…”
Section: Daymentioning
confidence: 99%